School's out- forever - Patterson, James, 1947- (Maximum Ride ;, 2006)
After a short stay with an FBI agent who gives them a chance to attend school and live a normal life, the six genetically-altered, winged youths head toward Florida and Max's ultimate destiny--to save the world, whether she wants to or not.